Selection of Tempoyak Lactic Acid Bacteria As Candidate Strain for Yoghurt Starter Culture - Hanum Mukti Rahayu; Mahwar Qurbaniah (Biosaintifika: Journal of Biology & Biology Education, 2019)
Selection of bacteria in yoghurt fermentation is important to produce yoghurt with good quality. Tempoyak lactic acid bacteria is potential to be yoghurt starter culture becouse tempoyak fermentation has similarities in producing lactic acid such as yoghurt. This study aimed to isolate and identify the lactic acid bacteria (LAB) from tempoyak which will be used as a yoghurt starter culture. The methods used in this study included isolation and selection of acid-producing bacteria, lactase and protease activity test, identification of morphology and biochemistry as well as testing the quality of the yoghurt. The results of the study obtained 32 isolates of the LAB with the same characteristic colony, include the round shape, cream-coloured with convex elevation and, smooth surface and entire edge. Selection of acid-producing bacteria obtained 12 isolates with the ability to produce clear zones on MRSA + CaCO3 media â‰¥ 0.7 cm. Selection of lactase-producing LAB obtained six strains and the protease test obtained two superior strains. Two superior strains namely Tp 12 and Tp 28 have characteristics of coccus, gram-positive, negative catalase, non-endospore and non-motile forms. The organoleptic and several quality tests showed yoghurt using Tp 12 as starter has higher acceptability, the highest levels of lactic acid and lactose levels with values respectively 4.25, 0.84% and 24.53%. This study obtained the LAB strain which can be used as yoghurt starter culture. Tp 12 strain can be used to improve the quality of yoghurt and become a commercial starter that can be applied to various fermented products.